Auditory‐Perceptual Speech Outcomes and Quality of Life after Total Laryngectomy. Issue 1 (24th September 2012) - Eadie, Tanya L.; Day, Adam M. B.; Sawin, Devon E.; Lamvik, Kristin; Doyle, Philip C.
Abstract : Objective: (1) To determine potential relationships between speech intelligibility, acceptability, and self‐reported quality of life (QOL) after total laryngectomy and (2) to determine whether relationships are stronger when QOL is measured by a head and neck cancer–specific or discipline‐specific QOL scale. Study Design: Cross‐sectional. Setting: University‐based laboratory and speech clinic. Subjects and Methods: Twenty‐five laryngectomized individuals completed disease‐specific (University of Washington Quality of Life; UW‐QOL) and discipline‐specific (Voice Handicap Index–10; VHI‐10) QOL scales. They also provided audio recordings that included the Sentence Intelligibility Test (SIT) and a reading passage. Thirty‐three listeners transcribed the SIT sentences to yield intelligibility scores. Fifteen additional listeners judged speech acceptability of the reading passage using rating scales. Results: The QOL scores were moderate across the UW‐QOL physical (mean = 77.63) and social‐emotional (mean = 78.02) subscales and the VHI‐10 (mean = 17.91). Speech acceptability and intelligibility varied across the samples, with acceptability only moderately related to intelligibility ( r = 0.41, P <. 05). Relationships were weak between ratings of intelligibility and self‐reported QOL (range, r = 0.00‐0.22) and weak to moderate between acceptability with QOL (range, r = 0.01‐0.46). The only statistically significant, but moderate, relationship was found between speech acceptability with the UW‐QOL speech subscore ( r = 0.46, P <. 05). Conclusion: Listeners' ratings of speech acceptability and intelligibility were not strongly predictive of disease‐specific or voice‐related QOL, suggesting that listener‐rated and patient‐reported outcomes are complementary.